Overview Of Students’ Entrepreneurial Interests Supporting Factors - Irdianti, Irdianti (Denisya Smart Consulting, 2024)
The aim of this research is to obtain an overview of the factors that can support the growth of entrepreneurial interest in students. The research method used in this research is a library research approach using 6 previous research articles related to students' interest in entrepreneurship. Based on the research results, it is known that the factors that influence students' interest in entrepreneurship come from internal and external factors. Internal factors, including motivation, creativity and innovation in students, have a joint influence on interest in entrepreneurship and play an active role in students' interest in entrepreneurship. Apart from that, external factors such as family environment; entrepreneurship education; income expectations; the use of social media and learning soft skills has a significant influence on students' interest in entrepreneurship. Furthermore, there will be expectations of greater income obtained from business. Furthermore, there are differences in entrepreneurial interest between male and female students.